ANALISIS DAYA DAN EFISIENSI TURBIN AIR KINETIS AKIBAT PERUBAHAN PUTARAN RUNNER - Muliawan, Arief; Yani, Ahmad (IAIN Batusangkar, 2016)
Research has been conducted about change power and efficiency on turbine. Manufacture of turbine singer aims to determine the magnitude of the reviews on power output and efficiency due to the rotation of the turbine runner. Turbine runner done with variation 90 rpm, 70 rpm, 50 rpm, 30 rpm and 10 rpm. Of the various rounds of runner that shows the maximum power change occurred on lap 50 rpm, 70 rpm and 90 rpm. Maximum power lead to speed with discharge runners 70 rpm flow 0.0078 m3 / s at 4,572 watts. Power generated minumum on debit 0.0078 m3 / s occurred on speed runner 90 rpm of 3,674 watts. Maximum turbine efficiency occurs debit on flow 0.0078 m3/s and 70 rpm with a value of 28.342%, and then declined in round 50 rpm amounted to 24.477% and the lowest in round 90 rpm amounted to 23.189%. From the calculation of the efficiency obtained maximum value is obtained at a speed of 70 rpm with a flow runner debit 0.0078 m3 / s.Key words: power, efficiency, kinetic turbines